2017
DOI: 10.1155/2017/8130796
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Subclinical Thyroid Dysfunction and the Risk of Cardiovascular Outcomes: A Systematic Review and Meta-Analysis of Prospective Cohort Studies

Abstract: Background Evidence on the association between subclinical thyroid dysfunction and the risk of cardiovascular outcomes are conflicting. Methods and Results PubMed, EMbase, Web of Science, Cochrane Library, and China Biology Medicine (CBM) databases were searched from inception to July 10, 2016. A total of 16 studies were included for meta-analysis. We found that subclinical hypothyroidism was not correlated with coronary heart disease (CHD) (RR = 1.17; 95% CI, 0.91–1.52), total mortality (RR = 1.02; 95% CI, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 55 publications
4
56
0
1
Order By: Relevance
“…Among the 52 included eligible MAs, 4628–73 (46/52, 88.5%) were published in English, and the rest74–79 (6/52, 11.5%) were published in Chinese. The 52 included MAs contained 685 studies, with an average of 13.2 (range: 3–39) studies per article.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 52 included eligible MAs, 4628–73 (46/52, 88.5%) were published in English, and the rest74–79 (6/52, 11.5%) were published in Chinese. The 52 included MAs contained 685 studies, with an average of 13.2 (range: 3–39) studies per article.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a recent retrospective study by Grossman et al demonstrated that SCH is associated with increased mortality in the elderly [11] . A recent review reported that SCH was not associated with increased risk of cardiovascular mortality or total mortality in the elderly [16] . However, owing to the relatively few studies, the result should be interpreted carefully and con rmed by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cohort study on 80,490 persons found that the association between SCH between all-cause or vascular mortality was stronger in men below 60 years compared to older males [23] . Another meta-analysis showed that the risk of the cardiovascular and all-cause mortality is higher in those mean age < 65 years than for those of average age ≥ 65 years [16] . All these results suggested that there may be age-related mortality difference associated with SCH, with stronger association in younger patients that attenuated advancing age.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported improvement in vascular and cardiac function and arterial stiffness in patients with SH 26, 27 . A meta-analysis showed a possible relationship between SH and an increased risk of coronary heart disease mortality compared with euthyroidism 28 . TRT was observed beneficial in preventing major adverse cardiovascular and cerebral events for hypothyroidism patients undergoing percutaneous coronary intervention 15 .…”
Section: Subclinical Hypothyroidismmentioning
confidence: 99%